Shock corridor - Breck, Peter; Towers, Constance; Fuller, Samuel, 1912-1997.; Cortez, Stanley; Dunlap, Paul, 1919-; Louriâe, Eugene; Evans, Gene, 1922-1998.; Thoms, Jerome; Best, James, 1926-; Rhodes, Hari.; Allied Artists Pictures Corporation; Home Vision (Firm); et al. ([S.l.] : Classic Collection, 1998)
A journalist gets himself admitted to a mental hospital to solve the murder of an inmate.
DVD format.
Originally released as a motion picture in 1963.
Letterbox format.
Producer, director and writer, Samuel Fuller ; music Paul Dunlap ; photography, Stanley Cortez.
Cast: Peter Breck, Constance Towers, Gene Evans, James Best, Hari Rhodes, Larry Tucker, William Zuckert, Philip Ahn, Neyle Morrow, Frank Gerstle, Paul Dubov, Rachel Romen, Linda Randolph, John Matthews, Chuck Roberson, John Craig.
MPAA rating: Not rated.
Keywords: Mental illness -- Drama; Psychiatric hospitals -- Drama; Journalists -- Drama; Feature films; Detective and mystery films